The Influence of Work Life Balance and Work Family Conflict on Employees' Job Satisfaction Through Burnout in Female Nurses at Mataram City Public Hospital - Baiq Rabiatul Adawiyah Kartika Wulan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Job satisfaction, stress levels, working conditions, competence, and compensation can affect hospital staff retention, including job satisfaction, stress levels, working conditions, and competence. Employees feel that their responsibilities are increasing as they start a new life as a family. In addition, employees often experience family problems that can affect their performance at work. Another problem that arises is the suboptimal implementation of work-life balance. There are employees who are unable to balance their work and personal lives, which have an impact on their less than optimal work performance. It is difficult to divide time between working in the hospital and working at home. This study aims to determine the effect of work-life balance on employee job satisfaction through burnout of female nurses at Mataram City Hospital and the effect of work-life balance on employee job satisfaction through Burnout of female nurses at Mataram City Hospital the impact of life balance. Researchers used a questionnaire designed to collect data, a survey was conducted on 348 female nurses. Using probability-based sampling techniques, 80 female nurses were selected as samples, and the data were analyzed using multiple linear regression analysis and the Sobel test. Thus, the following conclusions can be drawn as: 1) the results of the study indicate that the Work Life Balance variable has a negative and insignificant effect on job satisfaction in female nurses at Mataram City General Hospital. This means that Work Life Balance does not affect job satisfaction so that the proposed hypothesis is not accepted; 2) the results of the study indicate that the Work Family Conflict variable has a negative and insignificant effect on job satisfaction in female nurses at Mataram City General Hospital. This means that Work Family Conflict does not affect job satisfaction so that the proposed hypothesis is not accepted